2005
DOI: 10.2165/00003088-200544090-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Imatinib

Abstract: Imatinib is a potent and selective inhibitor of the protein tyrosine kinase Bcr-Abl, platelet-derived growth factor receptors (PDGFRalpha and PDGFRbeta) and KIT. Imatinib is approved for the treatment of chronic myeloid leukaemia (CML) and gastrointestinal stromal tumour (GIST), which have dysregulated activity of an imatinib-sensitive kinase as the underlying pathogenetic feature. Pharmacokinetic studies of imatinib in healthy volunteers and patients with CML, GIST and other cancers show that orally administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
481
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(528 citation statements)
references
References 58 publications
24
481
3
5
Order By: Relevance
“…The pharmacokinetics of imatinib has been extensively studied in Caucasian CML patients [17][18][19][20][21] . However, few studies have been reported on naïve Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetics of imatinib has been extensively studied in Caucasian CML patients [17][18][19][20][21] . However, few studies have been reported on naïve Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…Based on higher drug exposure in Chinese patients and dose-proportional imatinib exposure [18,19] , a rational conjecture is that Chinese patients would have a better disease response. We can infer that the patients in our studies had have better disease responses, even though CMR was not monitored in the IRIS study, in which BCR-ABL transcripts in the blood samples were measured only at 1 and 4 years in 124 patients who had a CCyR.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the number of patients in this study is small and that the study should be regarded as a pilot study. There might be a number of confounding factors such as different disease phase, that some patients were phenotyped during imatinib therapy and other factors might as well influence imatinib pharmacokinetics such as body weight and α-acid glycoprotein plasma levels [4,6,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, imatinib is metabolized mainly by cytochrome P450 (CYP) 3A4 and 3A5, although CYP1A1, CYP1A2, CYP1B1, CYP2D6, CYP2C9, and CYP2C19 might also contribute to a minor extent [4,5]. The main metabolite in plasma, CGP74588, is mainly formed by CYP3A4 and present in concentrations of around 20% of that of the parent drug but with a large interindividual variation.…”
Section: Introductionmentioning
confidence: 99%
“…These doses of imatinib have been shown to reach plasma concentrations comparable to those in CML patients treated with 400 mg imatinib daily. [20][21][22] For in vitro studies, 10 mM imatinib stock solutions in dimethylsulfoxide (DMSO; Fluka, Buchs, Switzerland) were frozen at Ϫ20°C. Indicated concentrations were added to the cell cultures.…”
Section: Imatinib Mesylate and Treatment Of Micementioning
confidence: 99%